2016
DOI: 10.1007/s10792-016-0395-0
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the management of Vogt–Koyanagi–Harada disease: sunset glow fundus is no more a fatality

Abstract: PurposeVogt–Koyanagi–Harada (VKH) disease is a primary autoimmune stromal choroiditis. Aim of the study was to gather a body of evidence from the literature and from experts that systemic corticosteroid combined with non-steroidal immunosuppressive therapy should become the standard of care in initial-onset VKH disease.MethodsLiterature was reviewed and leading experts in VKH were consulted in different parts of the world in order to put forward a consensus attitude in the management of initial-onset VKH disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
24

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 59 publications
1
25
0
24
Order By: Relevance
“…Taken together, the FA/ICGA scoring clearly showed that disease patterns and mechanisms in these two stromal choroiditis entities revealed some substantial differences. In contrast to BRC, where inflammation originated in parallel in both retina and choroid, in VKH disease, inflammation originated exclusively in the choroidal compartment, but then the intense and progressing choroiditis spread to neighboring structures (optic disc and retina) secondarily [23]. This sequence of events in VKH is important to acknowledge as it is crucial in understanding the very effective impact of therapeutic intervention on VKH and the evolution of the disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Taken together, the FA/ICGA scoring clearly showed that disease patterns and mechanisms in these two stromal choroiditis entities revealed some substantial differences. In contrast to BRC, where inflammation originated in parallel in both retina and choroid, in VKH disease, inflammation originated exclusively in the choroidal compartment, but then the intense and progressing choroiditis spread to neighboring structures (optic disc and retina) secondarily [23]. This sequence of events in VKH is important to acknowledge as it is crucial in understanding the very effective impact of therapeutic intervention on VKH and the evolution of the disease.…”
Section: Discussionmentioning
confidence: 98%
“…Treatment consisted of a combination of steroidal and nonsteroidal immunosuppressive therapy, with progressive tapering of the corticosteroids, within less than 6 months, and long-term maintenance of nonsteroidal immunosuppressive therapy [23].…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Therefore, herein we propose that, somehow, VKH disease has significant differences when first seen in the initial-onset acute or in the chronic recurrent stages. The recognition of these different courses of VKH disease carries weight because a diagnosis and proper treatment in the early stage imply a better prognosis and even a potential cure of the disease, since the main structure that generates inflammation at disease onset is the choroid and thus if inflammation is eradicated here, restoration of the blood-ocular barrier can be expected [ 39 , 40 ]. Accordingly, in most reports in the literature these two different stages (initial-onset acute and chronic recurrent disease), have shown completely different behavior as far as impact of therapy is concerned [ 39 , 40 ].…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…1. The deferral in the initiation of therapy because of diagnostic delay [64], especially in non-endemic areas. 2.…”
Section: Treatmentmentioning
confidence: 99%
“…The severity of VKH disease and its propensity to respond to treatment can be very diverse. In recent years, it has become increasingly clear that dual steroidal and nonsteroidal immunosuppressive IST is recommended, although a proportion of mild cases might be overtreated [64]. A 3-day course of intravenous methylprednisolone (500 to 1000 mg per day) is recommended followed by high-dose oral prednisone (1.0 to 1.2 mg/kg) for 4-6 weeks.…”
Section: Acute Uveitic Exudative Stage and Post-acute Stage (2 Months)mentioning
confidence: 99%